Faktor-faktor yang Mempengaruhi Peternak Ikut Serta dalam Program SPR di Kecamatan Tonra Kabupaten Bone - Nita Adillah Pratiwi; Khatifah; Besse Mahbuba We Tenri Gading; Weny Dwi Ningtyas; Andi Sukma Indah; Irmayanti; Ruth Dameria Haloho; Jisril Palayukan; Adli Putra Ermanda; Agni Ayudha Mahanani (Yayasan Perguruan Kampus, 2023)
The need for food rich in protein sources from livestock continues to increase from time to time, therefore it is very important for the government to pay attention to the availability of livestock through various programs, one of the programs chosen is the People's Livestock Center (SPR) program. The aim of this research is to determine the various factors that influence breeders who participate in the SPR program. The research method used is descriptive quantitative. The research population came from 3 villages in Tonra District, Bone Regency with a total population of 338 people. From the research results, data was obtained that there were at least 12 reasons for breeders participating in the SPR program with the most dominant factor being the desire to increase knowledge about animal feed processing at 28.2%.